Dilatation of Common Iliac Arteries after Endovascular Infrarenal Abdominal Aortic Repair with Bell-Bottom Extension - Telles,Gustavo José Politzer (2016)
Abstract Objective: Endovascular techniques to treat abdominal aortic aneurysms results in lower morbidity and mortality rates. However, dilation of the common iliac arteries prevents adequate distal sealing, which compromises the procedure success. The aim of this study is report the long-term outcomes of patients with abdominal aortic aneurysms associated with aneurysm of the common iliac artery following endovascular repair using a bifurcated bell-bottom stent graft. Methods: This is a retrospective study that evaluated patients treated with bifurcated bell-bottom extension stent grafts to repair an infrarenal abdominal aortic aneurysm and who had at least one common iliac artery with dilatation > 1.5 cm for at least 12 months after the endovascular intervention. Results: Thirty-eight patients with a mean age of 70.4±8.2 years were included. Stent graft placement was followed by dilation of the common iliac artery aneurysms in 35.3% of cases; endoleak and reoperation rates were 17.6% and 15.7%, respectively. Younger patients showed a higher rate of artery diameter increase following the procedure. The average arterial dilation was 16% in the first year, 29% in the second year, 57% in the third year and 95% from the fourth year until the end of follow-up. Conclusion: Repair of infrarenal abdominal aortic aneurysms with bifurcated bell-bottom type stents when there is common iliac artery dilation is a good therapeutic option to preserve hypogastric flow. The rate of endoleak was 17.6%, and 15.7% of cases required reoperation. Younger patients are more likely to experience dilation of the common iliac artery after the procedure.